Learning Design Subjects Of Criticism In Class IX Online and Offline MTsN 1 Sintang - Yuyu Wahyudin; Sukino; Erwin Mahrus (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2023)
The purpose of this study was to determine the suitability of the RPP for Akidah Akhlak class IX teachers with the principles of developing online and offline learning during the Covid 19 Pandemic based on KMA No 183 and KMA N0 184 of 2019 which were issued by the Minister of Religion of the Republic of Indonesia. In this study, the researcher attempted to interview a teacher of Akidah Akhlak at MTsN 1 Sintang whose name was Mrs. Suchudianti, S.Pd.I. She compiled a Learning Implementation Plan with the theme of Online and Offline Learning Tools for Akidah Akhlak Class IX for the 2021/2022 Academic Year.This type of research is field research, while the method used in this study is descriptive qualitative, namely the research produces descriptive data in the form of the suitability of the teacher's lesson plan with the principles of development based on KMA No. 183 and KMA No. 184 of 2019. The data and data sources in this study are in the form of 3 RPP Akidah Akhlak teachers from three (3) different Madrasas, namely 1) MIN 1, 2) MTsN 1 Sintang, and 3) MAN 1 Sintang. Data collection techniques in this study used techniques (1) document collection (2) interviews (3) observation. The results showed that the suitability of the teacher's lesson plan with the principles of elaborating the idea of KMA No. 183 and the syllabus was not appropriate because there were many factors that influenced it because the KMA included online student learning tools, namely using tools through the Whattsapp group, Goegle Meet, and E. Learning. Because during the Covid 19 pandemic all learning was carried out online, forcing all educational components to adapt to this very difficult situation. Parents are required to prepare tools for online learning, namely handponds so that children can learn remotely.